The Correlation Between Creativity and Discipline On Social Science Learning Outcomes - Afifah, Isa Ansori, Nur (Universitas Negeri Semarang, 2018)
This study aimed to assess the correlation between creativity and discipline toward social studies learning outcomes of 5rd grade students of State Elementary School Dwija Harapan Cluster, Sub-district Semarang. This research used quantitative method with correlation type. Samples were 129 students taken by using proportional random sampling. Data were collected by using interviews, questionnaires, and documentation. Data analysis technique was done through descriptive analysis, prerequisite analysis, and correlation analysis. The results showed that there was a significant correlation between creativity and discipline toward social studies learning outcomes which was proved by its value was 0.795. Thus, it could be concluded that there was a correlation between creativity and discipline toward social studies learning outcomes of 5rd grade students of State Elementary School Dwija Harapan Cluster, Sub-district Semarang.